The Prevalence and Prognostic Role of PD-L1 in Upper Tract Urothelial Carcinoma Patients Underwent Radical Nephroureterectomy: A Systematic Review and Meta-Analysis - Lu, Yi; Kang, Jiaqi; Luo, Zhiwen; Song, Yuxuan; Tian, Jia; Li, Zhongjia; Wang, Xiao; Liu, Li; Yang, Yongjiao; Liu, Xiaoqiang (Frontiers in Oncology, 2020)
Background: Several studies investigating the role of PD-L1 in upper tract urothelial carcinoma (UTUC) patients after radical nephroureterectomy (RNU) to predict prognosis had been published and great controversy existed among them. We, therefore, in the meta-analysis, reported the association between PD-L1 and survival in UTUC patients who underwent RNU. Methods: We searched the PubMed, Cochrane Library, EMBASE, and Web of Science by April 1, 2020. Hazard ratio (HR) and odds ratio (OR) were adopted to evaluate relationships between PD-L1 and survival outcomes, and tumor features, respectively. We formulated clinical questions and organized following the PICOS strategy. Results: Eight retrospective studies incorporating 1406 patients were included. The pooled positive rate of PD-L1 in UTUC patients was 21.0% (95% CI = 13.0–30.0%, I2 = 95.3%). Furthermore, higher PD-L1 in tumor tissues was related to shorter cancer-specific survival (CSS) in radically resected UTUC patients (HR = 1.63, 95% CI = 1.17–2.26, I2 = 0.0%), but was not associated with overall survival (OS) (HR = 1.49, 95% CI = 0.76–2.91, I2 = 74.9%). Subgroup analyses indicated associations between higher PD-L1 and shorter CSS in both Caucasus (HR = 1.72, 95% CI = 1.02–2.92, I2 = 0.0%) and Asian (HR = 1.57, 95% CI = 1.03–2.39, I2 = 23.1%) UTUC patients. Furthermore, PD-L1 was related to tumor grade of UTUC (High vs. Low, OR = 3.56, 95% CI = 1.82–6.97, P = 0.000) and invasive depth (pT3+pT4+pT2 vs. pT1+pTa/pTis, OR = 2.53, 95% CI = 1.07–5.96, P = 0.001). In the cumulative meta-analysis, results indicated that the 95% CIs narrowed as the pooled results gradually moved near the null. Conclusions: PD-L1 overexpression was related to worse survival outcomes in UTUC patients after RNU. It may be useful to incorporate PD-L1 into prognostic tools to select appropriate treatment strategies for UTUC. PD-L1 can also be clinically used for survival anticipation, risk stratification, and patient counseling. However, the pooled findings should be considered tentative until ascertained by more researches.